Current state of evidence of cannabis utilization for treatment of autism spectrum disorders - Agarwal, Rumi (BMC Psychiatry, 2019)
The core symptoms and co-morbidities associated with autism spectrum disorders (ASD) affect daily living and quality of life. Existing pharmacological interventions are only able to attenuate some related symptoms but are unable to address the underlying etiologies associated with ASD. Anecdotal evidence, which claims benefit from the use of cannabis to treat symptoms among this population, has been gaining popularity as families seek solutions. This paper analyzed recent peer-reviewed literature to identify the current state of evidence regarding cannabis use for the ASD population. Systematic reviews, reports, and experimental studies were assessed to understand the current extent and nature of the evidence on the risks and benefits of cannabis use for ASD. At this time, three large-scale clinical trials are currently at varying stages of progress and publication of results. Only five small studies were identified that have specifically examined cannabis use in ASD. Given the sparse state of evidence directly assessed in this population, studies which examined effects of cannabis on shared pathological symptoms of ASD such as hyperactivity, sleep disorders, self-injury, anxiety, behavioral problems, and communication were also reviewed. Studies revealed mixed and inconclusive findings of cannabis effects for all conditions, except epilepsy. Adverse outcomes were also reported, which included severe psychosis, increased agitation, somnolence, decreased appetite, and irritability. In addition, a wide range of cannabis compositions and dosage were identified within the studies, which impact generalizability. There is currently insufficient evidence for cannabis use in ASD, which creates an urgent need for additional large-scale controlled studies to increase understanding of risks and benefits and also to examine the impact of “entourage effects.” This will support discussions of treatment options between health care providers and ASD patients and their families. Evidence may lead to a desired new line of treatment or prevent adverse outcomes from unsubstantiated use amongst families aiming for symptom reduction.